A prospective study of adolescent pregnancy complications in a rural area of South India - Doddihal, Chandrika R.; Katti, Sangappa M. (International Journal of Research in Medical Sciences, 2017)
Background: Adolescent pregnancy is dangerous for the mother, child and the community and teenage girls are twice as likely to die of pregnancy and childbirth related complications as opposed to older women. Aim was to know the complications of adolescent pregnancies. And to study the socio-demographic profile of adolescent pregnancies. Methods: A total of 144 adolescent pregnant women, aged between 15-19 years were selected for the prospective study. Information on their socio-demographic variables and pregnancy complications was recorded during 3 study visits. The study was carried out at Vantamuri primary health centre-rural field practice area of J. N. medical college Belgaum, India for a period of 1 year. Results: In the current study majority, 66.0% participants were of 18-19 years age and were unemployed. Complications of pregnancy like PIH (4.3% versus 8.5%) and pre-term deliveries (22.4% versus 32.6%) were more seen in late adolescents. However, low birth weight was more in children born to young adolescents (42.6% versus 36.2%). Significant associations were found between age and anemia (p=0.013) and occupation (p=0.040) and socio-economic status (0.028) with mode of delivery. Conclusions: The mean age of participants was 17.8 years and complications like anemia, low birth weight, caesarean section and preterm deliveries varied with age of teens. Thus, periodic IEC activities must be held to improve their health.